2008
DOI: 10.1093/jmedent/45.6.1092
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and Molecular Analysis of Deltamethrin Resistance in the Common Bed Bug (Hemiptera: Cimicidae)

Abstract: This study establishes deltamethrin resistance in a common bed bug, Cimex lectularius L., population collected from New York City (NY-BB). The NY-BB population was 264-fold more resistant to 1% deltamethrin in contact bioassay compared with an insecticide-susceptible population collected in Florida (FL-BB). General esterase, glutathione S-transferase, and 7-ethoxycoumarin O-deethylase activities of NY-BB were not statistically different from those of FL-BB. cDNA fragments that encoded the open reading frame of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
103
0
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(109 citation statements)
references
References 44 publications
3
103
0
3
Order By: Relevance
“…Therefore, we were able to reassemble 67% of the draft genome into our putative LG, facilitating refinement and validation of the current genome assembly. In addition to constructing a genetic map, we detected a biallelic QTL on LG 12 that explains 64% of variation in pyrethroid resistance, in very close proximity (1.2 Mb) to a carboxylesterase encoding candidate gene for pyrethroid resistance (Zhu et al 2013; Benoit et al 2016), and <10 cM (but still within the 95% Bayesian credible interval) from the VSSC, another candidate strongly associated with insecticide survival in other studies (Yoon et al 2008, Zhu et al 2010). …”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Therefore, we were able to reassemble 67% of the draft genome into our putative LG, facilitating refinement and validation of the current genome assembly. In addition to constructing a genetic map, we detected a biallelic QTL on LG 12 that explains 64% of variation in pyrethroid resistance, in very close proximity (1.2 Mb) to a carboxylesterase encoding candidate gene for pyrethroid resistance (Zhu et al 2013; Benoit et al 2016), and <10 cM (but still within the 95% Bayesian credible interval) from the VSSC, another candidate strongly associated with insecticide survival in other studies (Yoon et al 2008, Zhu et al 2010). …”
Section: Discussionmentioning
confidence: 83%
“…Knockdown ( kdr ) resistance to pyrethroids is increasingly widespread in bed bugs ( e.g. , Zhu et al 2010), with kdr mutations at the target site of pyrethroids, the VSSC, identified as major mechanism for resistance (Yoon et al 2008). However, there is increasing evidence for a more complex basis for this trait, with penetrative (Mamidala et al 2012; Zhu et al 2013) and metabolic mechanisms (Zhu et al 2012), as well as behavioral avoidance (Romero et al 2009), associated with pyrethroid resistance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the L1014F or M918T mutation alone caused about a 5-10 fold reduction in the sensitivity of the DmNa v channel to deltamethrin, but the double mutations L1014F+M918T almost abolished the sensitivity of the DmNa v channel to deltamethrin (Lee et al, 1999; Vais et al, 2000). Similarly, the T929I mutation in combination with M827I and L932F completely eliminated the permethrin sensitivity of Vssc1 channels (Yoon et al, 2008). Two mutations, E435K and C785R, in the linker sequence connecting domains I and II are found to co-exist with L1014F in the cockroach.…”
Section: Naturally Occurring Mutations In Sodium Channels That Conmentioning
confidence: 99%
“…The two mutations marked with * alone do not confer pyrethroid resistance, but enhanced pyrethroid resistance mediated by L1014F or V410M. References on functional characterization of mutations in Xenopus oocytes are listed below: V410L/M (Oliveira et al, 2013; (Lee et al, 1999; Lee and Soderlund, 2001; Liu et al, 2002; Oliveira et al, 2013; Zhao et al, 2000); E435K + C785R + L1014F (Tan et al, 2002b); M827I, T929I and L932F (Usherwood et al, 2007; Vais et al, 2001; Yoon et al, 2008); M918T (Lee et al, 1999; Usherwood et al, 2005; Vais et al, 2001); L925I and I936V (Usherwood et al, 2007); L1014F/S/H (Burton et al, 2011; Du et al, 2013; Smith et al, 1997; Tan et al, 2002b; Tan et al, 2005; Usherwood et al, 2005; Vais et al, 2000); V1016G/I, I1011M/V, S989P , and D1763Y (Du et al, 2013); F1534C (Du et al, 2013; Hu et al, 2011); F1538I (Tan et al, 2005). …”
Section: Highlightsmentioning
confidence: 99%